日本における外来鳥類の寄生虫調査 - Yoshino, Tomoo; 4576; Kawakami, Kazuto; 4577; Hayama, Hisayo; 4578; Ichikawa, Noriyoshi; 4579; Azumano, Akinori; 4580; Nakamura, Shigeru; 4581; et al. (山階鳥類研究所, 2011)
Article A parasitological survey was performed on 11 species of birds introduced into Japan: Cygnus olor, Branta canadensis moffitti, Cairina moschata domestica, Phasianus colchicus karpowi, Bambusicola thoracica, Pavo cristatus, Psittacula krameri manillensis, Pycnonotus sinensis, Garrulax canorus, Leiothrix lutea, Lonchura malacca. A total of 17 taxa of external and internal parasites, including one protozoan (Eimeria sp.), five nematodes (Eucoleus perforans, Amidostomum anseris, Pseudaspidodera pavonis, Heterakis gallinarum and Synhimantus (Dispharynx) nasuta), four trematodes (Echinochasmus sp., Amphimerus anatis, Tanaisia sp. and Dicrocoeliidae gen. sp.), one cestode (unidentified) and six arthropods (Goniodes pavonis, Lipeurus maculosus, Ixodes turdus, Haemaphysalis flava, Leptotrombidium scutellare and Mouchetia sp.) were obtained and identified. Among the obtained parasites, Dicrocoeliidae gen. sp., I. turdus and L. scutellare from L. lutea, and Tanaisia sp. and L. scutellare from G. canorus, are the first host records, while P. pavonis and G. pavonis are the first geographical records from Japan. journal article